Repeated Intravenous Thrombolysis for Early Recurrent Stroke: Challenging the Exclusion Criterion - Kahles, Timo; Mono, Marie-Luise; Heldner, Mirjam Rachel; Baumgartner, Ralf Werner; Sarikaya, Hakan; Luft, Andreas; Bohlhalter, Stephan; Traenka, Christopher; Engelter, Stefan T.; Kurka, Natalia; Kohrmann, Martin; Curtze, Sami; et al. (Stroke, 2016)
Intravenous thrombolysis (IVT) within 4.5 hours from symptom onset improves functional outcome in patients with acute ischemic stroke. Its use in patients with previous stroke within the preceding 3 months is contraindicated because of the assumed higher risk of intracranial hemorrhage. In addition, tissue-type plasminogen activator may itself promote neurotoxicity and blood-brain barrier disruption. However, safety and effectiveness of repeated IVT is essentially unknown in patients with early (<3 months) recurrent stroke (ERS), because they were excluded from thrombolysis trials. This article reports the largest case series of repeated IVT in ERS.We reviewed databases of prospectively collected patient data of 8 European stroke centers for the presence of patients with ERS, who received IVT for both the index stroke and ERS. Demographics, clinical and radiological data, bleeding complications, and functional outcome were analyzed.We identified 19 subjects with repeated IVT in ERS. Mean age was 68±12 years, and 37% of them were female. Median interthrombolysis interval was 30 days (interquartile range, 13-50). Functional independence (modified Rankin scale score <=2) was achieved in 79% of patients after the first and in 47.4% after repeated IV tissue-type plasminogen activator, respectively. There was no symptomatic intracranial hemorrhage. Median final infarct volume after the first IVT was 1.5 cm(3) (interquartile range, 0.5-3.1).Patients with small infarct volumes and robust clinical improvement might be considered for repeated IVT within 3 months. Studies following strict protocols and larger registries incorporating these patients might serve to identify selection criteria for the safe use of repeated IVT in ERS.
EVALuna2:22476